Parent–School Collaboration in Developing Children’s Emotional Maturity - Febriana, Indah Ayu; Musripah, Musripah (Prodi Pendidikan Islam Anak Usia Dini STAI Darul Falah, 2025)
Emotions play an important role in human life because they influence patterns of thinking, behavior, and social interaction. In children, emotional development is influenced by both internal factors, such as physical and psychological conditions, and external factors, including parenting styles, learning experiences, and the school environment. This study aims to examine the role of collaboration between parents and teachers in fostering children’s emotional maturity. The study employed a descriptive qualitative approach, with research participants consisting of parents and teachers from a school in Pekalongan Regency. The findings indicate that harmonious collaboration between parents and teachers has a significant influence on children’s emotional development, particularly in their ability to develop self-awareness, regulate emotions, and cultivate empathy. The implementation of positive parenting practices within the family environment and social–emotional learning at school complements each other in shaping emotionally stable personalities in children. In addition, continuous communication between parents and teachers helps address various forms of maladaptive emotional behavior. Overall, this study confirms that synergy between parents and teachers is a key factor in optimizing children’s emotional development and has a positive impact on their social skills and academic achievement.